Expert consensus on re-irradiation for recurrent glioma - Krauze, Andra; Attia, Albert; Braunstein, Steve; Chan, Michael; Combs, Stephanie; Fietkau, Rainer; Fiveash, John; Flickinger, John; Grosu, Anca-Ligia; Howard, Steven; Nieder, Carsten; Niyazi, Maximilian; et al. (Radiation Oncology, 2017)
PURPOSE: To investigate radiation oncologists' opinions on important considerations to offering re-irradiation (re-RT) as a treatment option for recurrent glioma. MATERIALS AND METHODS: A survey was conducted with 13 radiation oncologists involved in the care of central nervous system tumor patients. The survey was comprised of 49 questions divided into 2 domains: a demographic section (10 questions) and a case section (5 re-RT cases with 5 to 6 questions representing one or several re-RT treatment dilemmas as may be encountered in the clinic). Respondents were asked to rate the relevance of various factors to offering re-RT, respond to the cases with a decision to offer re-RT vs. not, volume to be treated, margins to be employed, dose/fractionation suggested and any additional comments with respect to rationale in each scenario. RESULTS: Sixty nine percent of responders have been practicing for greater than 10 years and 61% have re-RT 20 to 100 patients to date, with 54% seeing 2-5 re-RT cases per month and retreating 1-2 patients per month. Recurrent tumor volume, time since previous radiation therapy, previously administered dose to organs at risk and patient performance status were rated by the majority of responders (85%, 92%, 77%, and 69% respectively) as extremely relevant or very relevant to offering re-RT as an option. CONCLUSION: The experts' practice of re-RT is still heterogeneous, reflecting the paucity of high-quality prospective data available for decision-making. Nevertheless, practicing radiation oncologists can support own decisions by referring to the cases found suitable for re-RT in this survey.
EVALuna2:32866